Enzymatic hydrolysis of banana agro-industrial waste to obtain a glucose syrup using Three pretreatments - Romero Bonilla, Hugo (2016)
The aim of this study was to compare three pretreatments (grinding, grinding + sodium hydroxide + 1%, and grinding + hydrothermal process) applied to peel ripe bananas (substrate) and its effect on the production of dextrose syrup by enzymatic hydrolysis the fungus Trichoderma ressei. Twenty seven cultures were prepared in different concentrations peel ripe bananas (40%, 50% and 60%) , factor A, subject to the three afore mentioned pretreatments , factor B. The biomass obtained was inoculated with conidia of the fungus Trichoderma ressei in a concentration of 0.2 ; 0.4 and 0.6 g/L , factor C, giving a 3x3x3 factorial experiment . Additionally, variation in these factors in time (four factors) was valued. Six days (144 hours) incubation at pH 4.2 - 5was performed at room temperature. The glucose concentration in the hydrolyzate was measured using the DNS method (di nitrosalisílic acid) in a UV visible spectrophotometer at 540 nm. The treatment produced a higher concentration of glucose , was T18 (sodium hydroxide milling plus - 60% ripe banana peel - 0.6 g/L yeast) six days after enzymatic hydrolysis with 5.91 g/L glucose, followed by 4.15 g/L T27 (more heating - milling 60% of ripe banana peel - 0.6 g/L of yeast) and 3.95 g / L of T9 (60% Shell grinding banana mature - 0.6 g/L of fungus) during the same time of experimentation.